Scientific And Theoretical Issues of Formation of Patriotic Skills in History Classes - Yusupov Zafar Usmanovich (Genius Journals, 2023)
The article focuses on bringing the scientific-theoretical and patriotism issues of formation of patriotism skills to the agenda .
Keywords: Abdulla Avloni; education; parents; upbringing